A Toxoplasma gondii vaccine encoding multistage antigens in conjunction with ubiquitin confers protective immunity to BALB/c mice against parasite infection - Yin, Huiquan (Parasit Vectors, 2015)
BACKGROUND: Toxoplasma gondii is a widely prevalent intracellular parasite which infects almost all warm-blooded animals including humans and causes serious zoonotic toxoplasmosis. DNA vaccines have proved effective in the protection against parasites. However, the problems of weak immunity and inefficient delivery of DNA vaccine remain major issues. Therefore, comprehensive antigens derived from all stages of the parasite, effective adjuvants and delivery systems should be considered in the vaccine construction. METHODS: SAG3(101–144),ROP18(347–396), MIC6(288–347), GRA7(182–224), MAG1(58–125), BAG1(156–211) andSPA(142–200), derived from antigens in tachyzoite, bradyzoite and sporozoite stages of T. gondii were screened based on CD8(+) T cell epitope binding affinity to HLA and H-2. We constructed a recombinant DNA vaccine and an adenovirus vaccine encoding multi-stage antigen of T. gondii linked to ubiquitin molecules and vaccinated BALB/cmice with different strategies. Antibodies, cytokines, splenocytes proliferation, as well as the percentage of CD4(+) and CD8(+) T cells in immunized mouse were analyzed by the Enzyme-Linked Immunosorbent Assays (ELISA), Flow Cytometry (FCM). Protective efficacy was evaluated by challenging immunized mice with type I and type II parasite. RESULTS: Our results indicated that the DNA vaccine had the advantage of inducing a stronger humoral response, whereas the adenovirus-vectored vaccine effectively improved the cellular immune response. Priming with DNA vaccine and boosting with adenovirus-vectored vaccine induced Th1-type immune responses with highest levels of IgG2a and secretion of cytokines IL-2 and IFN-γ. Effective protection against type I and type II parasite with an increase in survival rate and a decrease in brain cyst burden was achieved in immunized mice. CONCLUSIONS: Priming vaccination with DNA vaccine and boosting with the recombinant adenovirus vaccine encoding ubiquitin conjugated multi-stage antigens of T. gondii was proved to be a potential strategy against the infection of type I and type II parasite. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-015-1108-7) contains supplementary material, which is available to authorized users.